O01.2 Innate Immunity Modulation by Trichomonas Vaginalis Galectin-Binding Glycolipid Domains. (13th July 2013) - Fichorova, R N; Yamamoto, H S; Fashemi, T; Buck, O R; Foley, E; Hayes, G R; Sato, S; Singh, B N
Abstract : Background: Trichomonas vaginalis is a protozoan extracellular parasite causing long-lasting and recurrent vaginitis with a wide range of symptoms and increased risk of HIV and other viral STIs. The protozoan virulence factors that subvert the mucosal immune response are poorly understood. Here we investigate the role of the ceramide-phosphatidyl-inositol glycolipid core (CPI-GC) of the protozoan lipophosphoglycan (LPG), which is the major glycoconjugate on the trichomonad surface (2–3 million copies/parasite). We have previously determined that CPI-GC lacks mannose but contains polylactosamine repeats representing potential ligands for animal lectins called galectins, implicated in HIV pathogenesis. Methods: CPI-GC was isolated from T. vaginalis LPG by mild acid hydrolysis and C18-SepPak separation. Binding to galectin-1 and –3 (Gal-1 and –3) was determined by Biolayer Interferometry. Inflammation-related proteins and Gal-1 and 3 were measured by a multiplex immunoassay in supernatants from human cervical and vaginal epithelial cells infected with T. vaginalis or exposed to CPI-GC from different clinical isolates. Results: CPI-GC activated NF-κB and upregulated cFos, COX-2, IL-8, MIP-3α, IL-6, IL-1β and VEGF in a MEK1/2 dependent manner. In addition, IL-6, ICAM-1 and VEGF up-regulation was mediated by p38 while IL-8 and MIP-3α were ERK 1/2 mediated. CPI-GC from different clinical isolates varied in their ability to bind Gal-1 and Gal-3, which were constitutively expressed by vaginal and cervical epithelial cells and released at higher levels in the extracellular space during exposure to live trichomonas and CPI-GC. CPI-GC from all isolates invariably reduced levels of the natural microbicide SLPI. Mutant trichomonads that failed to bind Gal-1 and Gal-3 showed higher proinflammatory activity suggesting a role for the CPI-GC –galectin binding in suppressing innate immune responses. Conclusion: Interventions targeting CPI-GC or restoring the balance of natural immune defences represent a promising strategy for preventing adverse outcomes from T. vaginalis infection.